(untitled) (Research, Society and Development, 2020)
Social inequalities have always been present in Brazil, with the domination of some classes to the detriment of minorities. Throughout history, the events surrounding slavery, attacks on indigenous peoples, racism against blacks, and so many other cases have made it impossible to consider that the population is on an equal footing. Law No. 12,711, sanctioned by President Dilma Roussef in 2012, was an attempt to reduce such inequalities as it regulated the quota system in educational institutions. The objective of this article was to analyze the distribution of the vacancies offered in the selection process for the IFMT Integrated High School 2019/1 and to relate them to the admission options selected by the candidates. As a methodology, qualitative and quantitative exploratory methods were adopted, followed by bibliographic and documentary research procedures. The result of the analysis of the selection process data indicated that 2899 candidates, corresponding to 35.67%, opted for some type of quota throughout the IFMT. It was concluded that affirmative actions for access to Vocational and Technological Education contribute to the democratization of education.